Self-Responsibility Readdressed: Shifts in Financial Responsibility for Social Security Between the Public Realm, the Individual, and the Family in Europe. (January 2019) - Frericks, Patricia; Höppner, Julia
Self-responsibility is a prominent keyword in social policy and in welfare state reforms. The concept of self-responsibility, though, has never been clearly dissected for welfare state analysis. In particular, the debate on the turn toward self-responsibility in welfare states has not been adequately conceptualized, nor has the institutionalization of the family in welfare states been correspondingly analyzed, though all welfare states, to different degrees, apply family-related conditions to social rights. In other words, welfare states have treated individuals with family differently from individuals without family, and this has an impact on the interpretation of the turn toward self-responsibility. In this contribution, we systematically and comparatively analyze welfare state change in the family-related conditions applied to social rights, in order to identify shifts in financial responsibility for social rights from the public realm to either the individual or the family. We analyze changes occurring between 1993 and 2013 for two social security levels and two target groups in six European countries. Our findings show that trends toward reducing public financial responsibility, as in shifting financial responsibility for social security from the public realm back to citizens, have not prevailed. On the contrary, public financial responsibility for social rights has in part increased and in part been reshifted onto the family, so that self-responsibility is subsumed here under the concept of subsidiarity, and therewith refers to a nonindividualized "self". Citizens, in other words, are not increasingly conceived by welfare state regulations as isolated and self-reliant individuals, but as subjects embedded in both the public and family spheres.